Zn(II) and Cd(II)-based complexes for probing the enzymatic hydrolysis of Na4P2O7 by alkaline phosphatase in physiological conditions - Das, Priyadip; Sourish, Bhattacharya; Sandhya, Mishra; Das, Amitava (Chemical Communications, 2011)
Newly synthesized Zn(II) and Cd(II)-based complexes show unique selectivity towards inorganic pyrophosphate (PPi) in 100% aqueous medium at pH = 7.4 and act as a "turn-on" and "turn-off" real-time assay, respectively, for the evaluation of the enzymatic activity of alkaline phosphatase.